Towards the Education of the Future: Computational Thinking as a Generative Learning Mechanism - Eduardo SEGREDO; Gara MIRANDA; Coromoto LEÓN (Ediciones Universidad de Salamanca, 2017)
The transformation of traditional education into a Sensitive, Manageable, Adaptable, Responsive and Timely (SMART) education involves the comprehensive modernisation of all educational processes. For such a transformation, smart pedagogies are needed as a methodological issue while smart learning environments represent the technological issue, both having as an ultimate goal to cultivate smart learners. Smart learners need to develop 21st century skills so that they can become into smart citizens of our changing world. Technology and computers are an essential aspect for this modernisation, not only in terms of technological support for smart environments but also in terms of offering new methodologies for smart pedagogy and the development of smart skills. In this context, computational thinking appears as a promising mechanism to encourage core skills since it offers tools that fit learners' interests and gives them the possibility to better understand the foundations of our ICT-based society and environments. In this work, we raise to make an effort to encourage the development of computational thinking as an opportunity to transform traditional pedagogies to smarter methodologies. We provide a general background about computational thinking and analyse the current state-of-the-art of smart education, emphasizing that there is a lack of smart methodologies which can support the training of 21st century smart skills. Finally, we provide -to those educators interested in pursuing the philosophy of smart education- information about initiatives devoted to the dissemination or promotion of computational thinking; existing tools or materials which support educators for the development of computational thinking among the students; and previous experiences and results about the application of computational thinking in educational environments.